Neutrophil/Lymphocyte Ratio and Platelet/Lymphocyte Ratio in Branch Retinal Vein Occlusion - Zhu, Dan-dan (J Ophthalmol, 2019)
Purpose. To evaluate the neutrophil/lymphocyte ratio (NLR) and the platelet/lymphocyte ratio(PLR) value in the development of branch retinal vein occlusion (BRVO)patients. Methods. 81 patients with BRVO and 81 age and sex-matched subjects were recruited as the control group. The BRVO diagnosis was confirmed under comprehensive ophthalmologic examinations. NLR and PLR parameters obtained from peripheral blood were recorded. Results. Both the mean NLR and PLR was significantly higher in the BRVO group compared with the control group (p < 0.001). In ROC analysis, the AUC for NLR was 0.82, and NLR of >2.48 predicted BRVO with a sensitivity of 58% and specificity of 98%. The AUC for PLR was 0.78, and PLR of >110.2 predicted BRVO with a sensitivity of 72% and specificity of 72%. Conclusion. The current study demonstrated that BRVO patients had increased NLR and PLR levels compared with control subjects. The NLR and PLR may be used as independent predictors for identifying risk for the development of BRVO.